Development of an on-line solid phase disk extraction with capillary electrophoresis for the simutaneous separation and determination of fungicides - Wan Ibrahim, Wan Aini (Faculty of Science, 2005)
A method for the chiral separation of propiconazole, a triazole fungicide with two chiral centers, using cyclodextrin-modified micellar electrokinetic chromatography (CD-MEKC) with hydroxypropyl-γ-cyclodextrin (HP-γ-CD) as chiral selector was developed. The use of a mixture of 30 mM HP-γ-CD, 50 mM SDS, and methanol–acetonitrile 10%:5% (v/v) in 25 mM phosphate buffer solution was able to separate two enantiomeric pairs of propiconazole. Stacking and sweeping-CD-MEKC under neutral pH (pH 7.0) and under acidic condition (pH 3.0) were used as two on-line preconcentration methods to increase detection sensitivity of propiconazole. Good repeatabilities in the migration time, peak area and peak height were obtained in terms of relative standard deviation (RSD). Sweeping-CDMEKC at acidic pH was found to give the highest sensitivity (100-fold) and the method was applied to the chiral separation of propiconazole enantiomers and two other triazole fungicides, namely fenbuconazole and tebuconazole (triazole fungicides with one chiral center). The limits of detection for the three triazole fungicides ranged from 0.09 to 0.10 mg/L, which is well below the maximum residue limits (MRL) set by Codex Alimentarius Commission (CAC). Combination of solidphase extraction (SPE) pretreatment and sweeping-CD-MEKC procedure was applied to the determination of three triazole fungicides (fenbuconazole, tebuconazole and propiconazole) in grapes samples spiked at concentrations 10–40 times lower than the MRL established by the CAC. The average recoveries of the selected fungicides in spiked grapes samples were good, ranging from 73% to 109% with RSD of 9–12% (n = 3). MEKC was also used for the separation of four fungicides (carbendazim, thiabendazole, propiconazole and vinclozolin). It was found that 20 mM formate buffer pH 7, 60 mM sodium cholate and 25 kV voltages gave the best condition for separation. All fungicides can be separated and gave one peak except for propiconazole with two stereoisomer peaks.